Peran Electronic Word Of Mouth Memediasi Pengaruh User Generated Content terhadap Purchase Intention: Studi pada Konsumen Gen-Z Produk Parfum HMNS - Anak Agung Gede Mahardika Juliananda; Ni Made Rastini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The Indonesian local perfume industry has experienced a marketing transformation due to the increasing use of digital platforms by Generation Z consumers. HMNS, as the market leader in local perfumes, faces challenges in increasing purchase intention in Denpasar despite extensive digital exposure. User Generated Content (UGC) contributes to shaping consumer perceptions through authentic and experience-based information, but its influence on purchase intention is often indirect. Therefore, electronic Word of Mouth (eWOM) is considered a mediating variable that strengthens consumer trust through social validation in digital media. This study aims to analyze the effect of UGC on purchase intention, the effect of UGC on eWOM, and the mediating role of eWOM in the relationship between UGC and purchase intention among Generation Z consumers of HMNS perfumes in Denpasar City. Data were collected through questionnaires using a non-probability sampling technique and analyzed using Partial Least Squares (PLS). The results indicate that UGC has a positive and significant effect on both eWOM and purchase intention, while eWOM partially mediates the relationship between UGC and purchase intention. These findings highlight the importance of authentic digital content and consumer recommendations in strengthening purchase intention.